The Nefarious hierarchy: An alternative new theory of the firm - Richard J. Arend (Administrative Sciences, 2021)
We propose a new theory of the firm based on the premise that "the firm" characterizes a factor-integrative form of doing business that is often the most effective and efficient structure for doing well by doing bad. We define the terms and requirements involved for such a theory, and fulfill those requirements by explaining what it is "to do bad", and why and when the firm form is especially fitted to that. We do so by building upon basic premises about "bad-ness" and by leveraging the logic of market failures. From this base, we argue a new reason for the firm form to exist and yet be limited in its growth. This leads to six related propositions regarding the relationships between "bad" firms, tolerant contexts and realized social harms. We discuss how to test the ideas, and what the implications are for research on the firm, strategy and entrepreneurship.
Keywords: 350; entrepreneurship; ethics; firm performance differences; governance choice/ form; nefariousness; theory of the firm